(untitled) (American Journal of Islam and Society, 2011)
With the uprisings in the Middle East and North Africa come scores of intellectual initiatives and academic investigations geared toward understanding the forces and motives propelling these unprecedented developments. Conferences are being convened and special issues of journals are being dedicated to addressing some aspects of the current phenomena ‒ not to talk of droves of “experts” (academic tourists?) pouring into the Muslim world for research. In short, the so-called “Arab Spring” ‒ also known by the people from the region as revolution (thawra), uprising (intifāÌa), renaissance (nahÌa) and awakening (ṣaḥwa)1 ‒ has been an intellectual treasure trove for academics in the areas of Middle Eastern Studies, Islamic Studies, and Comparative Politics. But are the attempts to explain these phenomena enough to guide the present and future Muslim generations to proper trajectories toward sociopolitical and intellectual success? This editorial is intended to argue that, despite the potential positive outcomes from recent initiatives, now is the opportune time for Muslims to seize in order to design future trajectories for their upcoming generations. The sociopolitical imperatives (civility, freedom, empowerment, pluralism, and happiness, to name a few), to which they aspire to respond, must be guided by, or anchored in, grand intellectual endeavors ...